Association Between Epidural Analgesia and Cancer Recurrence or Survival After Surgery for Renal Cell Carcinoma: A Propensity Weighted Analysis - Yen, Fang-Yu; Chang, Wen-Kuei; Lin, Shih-Pin; Lin, Tzu-Ping; Chang, Kuang-Yi (Frontiers in Medicine, 2022)
Whether epidural anesthesia and analgesia (EA) is beneficial for postoperative cancer outcomes remains controversial and we conducted this historical cohort study to evaluate the association between EA and long-term outcomes following surgery for renal cell carcinoma (RCC). We collected patients receiving RCC surgery from 2011 to 2017 and followed up them until February 2020. Patient attributes, surgical factors and pathological features were gathered through electronic medical chart review. The association between EA and recurrence-free and overall survival after surgery was evaluated using Cox regression models with inverse probability of treatment weighting (IPTW) to balance the observed covariates. The median follow-up time for the 725 included patients was 50 months (interquartile range: 25.3–66.5) and 145 of them (20%) received perioperative EA. We demonstrated EA use was associated with better recurrence-free survival (IPTW adjusted hazard ratio (HR): 0.64, 95% confidence interval (CI): 0.49–0.83, p < 0.001) and overall survival (IPTW adjusted HR: 0.66, 95% CI: 0.49–0.89, p = 0.006) in patients receiving surgical resection for RCC. More prospective studies are needed to verify this connection between EA and superior cancer outcomes after RCC surgery.